Evaluation of Citral and Green Silver Nanoparticles From Cymbopogon citratus Extract on Biochemical Profile and Nrf2 Gene Expression in Liver Tissue of Type 2 Diabetic Rats. - Khatinasab, Shadi; Kazemipour, Nasrin; Noorbakhsh, Mohammad Foad; Nazifi, Saeed; Faraji, Milad; Ahmadi, Nasrollah; Badraoui, Riadh (BioMed Research International, 2025)
The aim of this study was to evaluate the antioxidant effects of Cymbopogon citratus, citral, and green‐synthesized silver nanoparticles derived from the extract in mitigating oxidative stress–induced liver damage in diabetes mellitus. Seventy rats were randomly split into seven groups: a control group of healthy rats received normal saline, a cosolvent group of Type 2 diabetics received olive oil, a negative control group of Type 2 diabetics, and groups of diabetic rats receiving various treatments: metformin (100 mg/kg), Cymbopogon citratus extract (30 mg/kg), citral (30 mg/kg), and green‐synthesized silver nanoparticles (30 mg/kg). Type 2 diabetes was induced in rats using 90 mg/kg of nicotinamide and 65 mg/kg of streptozotocin. After 6 weeks, the rats were anesthetized to extract blood samples. The serum levels of the liver function test (serum glutamic–oxaloacetic transaminase, serum glutamic–pyruvic transaminase, and alkaline phosphatase) were measured. They were then euthanized by CO2 inhalation. Liver tissue was used to investigate histopathology, antioxidant activity, and Nrf2 gene expression. In the diabetes group, liver function tests increased, while TAC decreased and MDA increased (p < 0.05). The expression of the Nrf2 gene decreased compared to the control group (p < 0.05). In the treatment groups, the liver function tests and MDA decreased, while TAC and the expression of the Nrf2 gene increased compared to the Type 2 diabetes group (p < 0.05). The histopathological examination showed a return to normal condition. The study found that Cymbopogon citratus, specifically citral and green‐synthesized silver nanoparticles, effectively mitigated oxidative stress–induced liver damage in diabetes.